Heavy vehicles and roads technology, safety and policy : proceedings of the Third International Symposium on Heavy Vehicle Weights and Dimensions organised by the University of Cambridge and held at Queens' College, Cambridge, UK on 28 June-2 July 1992 - Cebon, David; Mitchell, C. G. B. (Thomas Telford, 1992)
Looks at the civil engineering and mechanical engineering aspects of the heavy vehicle/infrastructure system. The state of the art in research and implementation on issues such as highway geometry, traffic management, enforcement technologies and safety are reviewed.